Biblioteca digital: uma proposta para publicação e disseminação do conhecimento produzido através das teses e dissertações - Gubiani, Juçara Salete (2005)
With the coming of the World Wide Web (Web), there has been a great change in the form of communication between the people and the organizations. The link among documents that can be situated in any place on the computer network, through the Internet and the concept of Universal Resource Locator, made the fast recovery of information possible, before materialized in environments of restricted access. Publishing on Internet has become a simple task, however it was necessary to search for quality in publications and an only vestibule of access and search of excellent information. Proposals with standards for publication have appeared propitiating the interoperabilidade of information. In this context we have the digital libraries offering conditions to make a great net of data and knowledge. This work has the aim to analyze technologies for publication on the Web and to suggest a proposal to publish the knowledge produced through the Theses and Dissertation of the Programs of Pos-Graduation of the Federal University of Santa Maria (UFSM), as well as measuring the acceptability in the academic community of the new form of spreading and dissemination of the knowledge. The proposal tool must use standards and technologies that offer total integration with the other libraries in the country and be part of the project of the Digital Library of Theses and Dissertations (BDTD), as well as being linked with the Digital Networked Library of Theses and Dissertations of Virginia Tech University. After analysis of technologies, publication protocols and the view of the academic community, the system TEDE developed by the Institute of Science and Technology (IBICT), was considered as solution for publication. It was chosen because it incorporates technologies with protocols capable to collect and to make the transference of information possible being guaranteed the necessary interoperabilidade among libraries and for consequence the dissemination of the knowledge produced by the programs of pos-graduation through the publication of the theses and dissertations on the Web.